2007
DOI: 10.1007/s00726-007-0505-4
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the metastatic activity of melanoma cells by transglutaminase-catalyzed incorporation of polyamines into laminin and Matrigel

Abstract: Previously published evidences highlighted the effect of transglutaminase (TG, EC 2.3.2.13) activation on the reduction of the in vitro adhesive and invasive behaviour of murine B16-F10 melanoma cells, as well as in vivo. Here, we investigated the influence of spermidine (SPD) incorporation by TG into basement membrane components i.e. laminin (LN) or Matrigel (MG), on the adhesion and invasion of B16-F10 melanoma cells by these TG/SPD-modified substrates. The adhesion assays showed that cell binding to the TG/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Although the results demonstrated the presence of protein-bound polyamines in these cancer cells, pronounced differences were observed in the two cell lines investigated (Beninati et al 1993). The role of the post-translational modification of ECM and basement membrane proteins with polyamines in the metastatic process, catalyzed by an activated TG2, has been extensively investigated in B16-F10 murine melanoma cells (Lentini et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Although the results demonstrated the presence of protein-bound polyamines in these cancer cells, pronounced differences were observed in the two cell lines investigated (Beninati et al 1993). The role of the post-translational modification of ECM and basement membrane proteins with polyamines in the metastatic process, catalyzed by an activated TG2, has been extensively investigated in B16-F10 murine melanoma cells (Lentini et al 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, the metastatic efficacy also depends critically upon the ability of tumor cells to breach basement membranes by elaborating and secreting matrix metalloproteinases MMP-2 and MMP-9. [28][29][30][31] The increased production of active MMP-2 and MMP-9 also contributes to the enhanced metastatic potential of remnant tumor cells after immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies from Mehta and his colleagues have shown that TG2 increases the invasiveness and metastatic capacity of certain cancer cells [89, 137, 138]. It should be noted however, that any increase in metastatic capacity is most likely mediated by the scaffolding function of TG2, and when transamidating activity is involved, TG2 might actually decrease the migration and invasion [139, 140]. Evidence is accumulating showing the role of TG2 on the migration of inflammatory cells.…”
Section: Cell Surface Tg2: a Cue For Survival Proliferation And Mmentioning
confidence: 99%